Diblock metallocopolymers containing various iron sandwich complexes: living ROMP synthesis and selective reversible oxidation. Issue 13 (7th March 2016) - Gu, Haibin; Ciganda, Roberto; Hernández, Ricardo; Castel, Patricia; Vax, Amélie; Zhao, Pengxiang; Ruiz, Jaime; Astruc, Didier
Abstract : New diblock copolymers containing two iron-sandwich complexes in the side chain have been synthesized and oxidized to obtain mixed-valent Fe II –Fe III copolymers. Abstract : The design of redox-robust metallocopolymers is expected to produce new nanomaterials with multiple applications. Here the ROMP syntheses using Grubbs' 3 rd generation catalyst of three new living diblock copolymers each containing two distinct redox-stable iron sandwich complexes of the ferrocene, pentamethylferrocene and cyclopentadienyl-iron-arene families in the side chain are reported. The electrochemical properties of these diblock metallocopolymers investigated by cyclic voltammetry show complete chemical and electrochemical reversibilities of the redox waves, which also allow using the Bard–Anson method to determine the number of monomer units. The selective and reversible "chemical" oxidation of one of the blocks in two of these metallocopolymers afforded the syntheses of mixed-valent Fe II Fe III polymers.